Texte und Kontexte Analysen zum neueren spanischen Roman und Essay - Rien, Horst (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
By applying the theoretical concepts of 'discourse' and 'mental schema' to textual analysis, the author presents an innovative analysis of important Spanish novels and essays from the recent past, focusing on the relationship between literary text and collective knowledge. Considering aspects such as power, memory, modernisation, etc., he brings to light contextual references between literary and non-literary contemporary texts and consequent correlations between literary and social developments. This volume is aimed primarily at literary and cultural scholars. Horst Rien, born in 1948, is a Romance scholar who has taught at the universities of Göttingen and Hamburg. His research focuses on Spanish and French literature from the 18th and 20th centuries.